Antimony oxide minerals from Hungary - Szakáll Sándor (Acta mineralogica-petrographica, 2000)
Most of the Hungarian stibnite and fahlore occurrences contain antimony-bearing weathering products that earlier were either unidentified or their identification was doubtful. All these occurrences were investigated by using XRPD and EDS for the identification of the substances in question. The results of investigations are reported here together with a brief description of the Hungarian stibnite occurrences, the antimony-bearing weathering products and their mineral assemblages. Occurrences of stibnite and antimony oxides are shown in Fig. 1. A list of Hungarian stibnite localities arranged according to mountains is given in Table 1 and a list of antimony oxide minerals is given in Table 2 Cervantite, in spite of being reported most frequently from this mineral group in the Hungarian mineralogical literature, has been found to occur only in Gyöngyösoroszi. On the other hand, stibiconite proved to be ubiquitous, and several new occurrences of bindheimite were also found. Our investigations confirmed the occurrences of Valentini te and tripuhyite in Hungary and the first occurrence of partzite is also described.